Gelatinase-responsive release of an antibacterial photodynamic peptide against Staphylococcus aureus. (26th March 2021) - Qiu, Lin; Wang, Cheng; Lei, Xiaoling; Du, Xuancheng; Guo, Qianqian; Zhou, Shuwen; Cui, Pengfei; Hong, Tingting; Jiang, Pengju; Wang, Jianhao; Li, Yong-Qiang; Xia, Jiang
Abstract : GRAPN releases APP in response to the gelatinase secreted by S. aureus, and accelerates the healing of infected wounds. Abstract : Staphylococcus aureus ( S. aureus ) related staphylococcal infection is one of the most common types of hospital-acquired infections, which requires selective and effective treatment in clinical practice. Considering gelatinase as a characteristic feature of S. aureus, gelatinase-responsive release of the antibiotic reagent thereby can target the pathogenic S. aureus while sparing beneficial bacteria in the microflora. In this work, we design a hybrid antibacterial photodynamic peptide (APP, Ce6-GKRWWKWWRRPLGVRGC) based on the polycationic antimicrobial peptide GKRWWKWWRR by introducing a photosensitizer chlorin e6 (Ce6) at the N-terminus, a cysteine residue at the C-terminus, and a gelatinase cleavage site (PLGVRG) inserted between the C-terminal cysteine and the polycationic peptide. This multi-motif peptide assembles with gold nanoclusters (AuNc) via Au–thiol bonding and affords a gelatinase-responsive antibacterial photodynamic nanocomposite (GRAPN). In vitro results show that the gelatinase secreted by S. aureus can cleave and release APP from AuNc, thereby resulting in preferential killing of S. aureus over E. coli . In a mouse model of staphylococcal skin wound infection, by integrating gelatinase-responsive drug release and the synergistic effect of a photodynamic agent and APP, GRAPN exhibits a marked photodynamic antibacterial activity, effectively eradicates S. aureus infection, and promotes rapid healing of the infected wounds.